Sacred Places, Economic Risk, and the Moral Economy of the Peasant in Late Antique Hispania - Suárez Vallejo, Rocío; Suárez Vallejo, Rocío (My University, 2021)
As part of the panel “Negotiating the Crisis: the Role of Sanctuaries as Places of Resilient Religious Experiences”, our contribution aims at analysing the role of sacred places in rural areas of Late Antique Hispania to cope with perceived economic risk. Loosely following the track of De Martino’s concept “crisis of the presence”, this panel is focused, among other key questions, on how sanctuaries and sacred places acted as netdoms in which daily-life crisis situations intermingled with other sets of religious experience, with consolidated and “in the making” religious narratives–related to that particular place, the rituals that took place there and the sacred objects stored there–, or with social encounters that reproduced, reinforced or contested the hegemonic dynamics of local power relations.
Keywords: Hispania -- Economía; History of Religions; Moral Economy; Rural Religion; Late antique religions